TEKNOLOGI PEMANFAATAN PASIR GUNUNG SEBAGAI PUPUK ALAMI: MEMPERCEPAT PELEPASAN UNSUR HARA - Iskandar Iskandar; Indah Irwanti (Departemen Ilmu Tanah dan Sumberdaya Lahan, Fakultas Pertanian, IPB University, 2003)
Volcanic sands, that contain relatively high content of dark minerals. can be used as a natural fertilizer. Unfortunately, the amount of the nutrients from this material available for the plant growth is very low. To increase the release of the nutrients to the environment. weathering process of the minerals should be accelerated. The objective of this research was to study the capability of urea and ammonium sulphate (ZA) in increasing the release of cations Ca2, Mg2, K1, Cu2 and Zn2 from the minerals. Urea and ZA used in this study is not only known as the source of N fertilizer but also found to destroy the floor of the storehouse made from concrete. Volcanic sands from Cimangkok and Ciapus were sieved with 100 mesh sieve and were mixed with each urea or ZA with the rate of 10%, 20% and 33%. The mixture was then 3 months incubated in wet conditions. The amount of Ca2 , Mg2, K1, Cu2 and Zn2 extracted with aquadest was measured at the 1st, 2nd and 3rd months. Due to the higher acidity, adding df the ZA to the sand from Cimangkok and Ciapus effectively increased the amount of extracted Ca2, Mg2 and K1 compared to the adding of urea. At the rate of 10%, adding of the ZA to the sand from Ciapus increased the amount of extracted Ca2 from 25.3 mg kg-1 to 800.1 mg kg-1 and K from 10.6 mg kg-1 to 108.3 mg kg-1. The highest concentration of Mg2 was found on the treatment of ZA with a rate of 33%. i.e. from 9.8 mg kg-1 to 161.7 mg kg-1 in sand from Ciapus. Adding of the urea or of the ZA affected the amount of extracted Cu2 and Zn2, however, there was no trend which rate effectively have increased the extracted these cations. Generally, the incubation time of I, 2 or 3 months is not significantly effected the amount of extracted cations. Keywords: Ammonium sulphate (ZA). natural fertilizer. nutrient, volcanic sand, urea